Use some of the scheduling rules for nursing staffs to improve operational performance _ Applied Research in al- Shahed al-Sadr General Hospital - ماجود هالة حمد; حرفش نور كريم (Journal of Economics and Administrative Sciences, 2017)
Hospitals are part of the service organizations and most importantly at the level of individuals because they are tied to the people health and their daily lives , the nursing service is one of the important services provided by hospitals, and nurses are the human resource that offers this service, from this standpoint the idea of ​​research came to prepare work Scheduling for nurses in a scientific way to improve performance operational for their services and provide efficient service available 24 hours a day, the research use one of the modern and scientific rules of scheduling its “schedule of working days and holidays rule for workers” , and applied on the nurses at AI Sahed al-Sadr General Hospital in Baghdad, the methodology of research adopted the applied and analytical research , and the data collected from the reality of installed information in the records of patient and records archive for nurses to preparing weekly work schedules for nurses and measure and analyze operational performance levels First, according to the numbers of nurses in scheduling Applied in hospital, and then measure the performance levels According to the number of nurses in the scientific scheduling proposed in research, The research found a number of results the most important that nurses scheduling that applied in the hospital not fit with the levels of demand for nursing service in the most of its divisions. research concluded a number of recommendations, the most prominent is the move away from discretionary methods of scheduling and application of scientific method of scheduling that proposed by the research because it has proven its effectiveness in contributing to the improvement of the operational performance.